Perbedaan Kepercayaan Diri Siswa yang Aktif Pramuka dan yang Tidak Aktif Pramuka - A Maulani Habibi; Fadzlul Fadzlul (Universitas Ahmad Dahlan, 2016)
This study aimed to find out the self-confidence difference between the active and inactive students scout. This was a comparative study with 100 samples taken by using simple random sampling technique. The instrument used in this study is a self-confidence questionnaire. This study employed independent sample t-test to analyze the data. The result of this study showed that the difference of self-confidence on active and inactive student scout in SMPN 5 Kota Jambi through t count was 3,868 > t table 2,022. In other words, there was a difference of self-confidence on the students who actively participated in Scout and those who did not. The result of this study is recommended for the school counselor to assist the students with low self-confidence.